2019
DOI: 10.1016/j.heliyon.2019.e02565
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetic properties of HIV-1 protease inhibitors: A computational perspective on herbal phytochemicals

Abstract: Acquired Immune Deficiency Syndrome is the most severe phase of Human Immunodeficiency Virus (HIV) infection. Recent studies have seen an effort to isolate phytochemicals from plants to repress HIV, but less studies have focused on the effects of these phytochemicals on the activities of enzymes/transporters involved in the metabolism of these drugs, which is one of the aims of this study and, to examine the antiviral activity of these compounds against HIV-1 protease enzyme using computational tools. Centre o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 46 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…Receptor-ligand interaction examined the molecular interactions between the bound molecules and the amino acid residues at the active sites of the enzyme (Chetty et al, 2016 ; Idowu et al, 2019 ). Figures 3–5 showed the 2 D visualisation of the interactions between the molecules and active site residues of COVID-19 M pro , COVID-19 S gp and the types of interactions (such as hydrogen bond, π-sigma, π-cation, π-Sulfur, π-alkyl, π-π stacked interaction, donor-donor interactions and Van der Waals (vdW) overlaps) observed in the interaction plots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Receptor-ligand interaction examined the molecular interactions between the bound molecules and the amino acid residues at the active sites of the enzyme (Chetty et al, 2016 ; Idowu et al, 2019 ). Figures 3–5 showed the 2 D visualisation of the interactions between the molecules and active site residues of COVID-19 M pro , COVID-19 S gp and the types of interactions (such as hydrogen bond, π-sigma, π-cation, π-Sulfur, π-alkyl, π-π stacked interaction, donor-donor interactions and Van der Waals (vdW) overlaps) observed in the interaction plots.…”
Section: Resultsmentioning
confidence: 99%
“…The MD simulation was performed as described by Idowu et al ( 2019 ). The simulations were performed using the GPU version provided with the AMBER package (AMBER 18), in which the FF18SB variant of the AMBER force field (Nair & Miners, 2014 ) was used to describe the systems.…”
Section: Methodsmentioning
confidence: 99%
“…Mature HIV-1 protease exists as a 22 KDa homodimer, each one containing an Asp25 amino acid, which acts as the catalytic residues are able to hydrolyze peptide bonds on the Gag-Pol polyproteins into fully functional viral proteins, like reverse transcriptase and integrase. Kehinde et al (2019) [ 27 ] showed that the phytochemicals kaempferol-7- O -glucoside and EGCG were able to interact with HIV-1 protease, showing pronounced structural evidence as potential HIV-1 protease inhibitors ( Figure 4 ). Interestingly, phytochemicals can also be used to reduce the extrusion of antiviral drugs from infected cells.…”
Section: Insights Into Flavonoid Molecular Targets and Antiviral Smentioning
confidence: 99%
“…Interestingly, phytochemicals can also be used to reduce the extrusion of antiviral drugs from infected cells. In fact, apigenin, fisetin and luteolin were able to slow down the elimination of the antiviral drugs atazanavir, lopinavir, darunavir and saquinavir, which target the viral protease of HIV-1 [ 27 ].…”
Section: Insights Into Flavonoid Molecular Targets and Antiviral Smentioning
confidence: 99%
“…The extensive study on these natural phytochemicals also showed great results against other viruses like dengue, HIV, malaria, etc. [ 18 , 43 ]. Many of these compounds are indicated in the literature to have pharmacological properties [ 48 ].…”
Section: Molecular Docking Analysismentioning
confidence: 99%